Intellectual Property Rights Crises in the Light of Digital Technology - Kheira Mousseddek; Assia Hachmaoui (Journal of Science and Knowledge Horizons, 2025)
Due to the rapid technological development that the world is witnessing today, all areas of human activity, including law, have been affected, leading to the creation of a virtual space parallel to the real space. Therefore, intellectual property legal systems have undergone several changes to face the outcomes of technology implementation.Current theoretical research seeks to determine the extent to which current intellectual property systems are sufficient to ensure effective legal protection for digital works. It addresses two aspects of the crises in this digital era: the inability of copyright law to effectively and seriously protect digital works, and the inadequacy of the copyright system to protect software. This paper discusses the effectiveness of granting a patent for software by presenting the experiences of many leading countries in the field.